2015
DOI: 10.1108/jmtm-11-2014-0118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lean practices on performance measures in context to Indian machine tool industry

Abstract: Purpose – The purpose of this paper is to investigate the impact of lean production practices on performance measures in machine tool industry and determines the lean criteria that can have significant positive impact on performance. Design/methodology/approach – The research paper presents a blend of theoretical framework and practical applications. Extant literature was reviewed and to achieve the research objectives, an exploratory su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 54 publications
0
76
0
2
Order By: Relevance
“…Time-based competition, lot sizing (production in small/large batches), continuous flow production and bottleneck removal are lean practices identified by de Treville et al (2004) to contribute positively in the reduction of lead times. Sharma et al (2015) performed multiple regression analysis to evaluate the impact of several lean manufacturing practices on lead time (The manufacturing practices being the independent variables). In their research, pull system was discovered to be a positive predictor (Nakamura et al, 1998;Sharma et al, 2015;Singh et al, 2013) while set up time reduction was observed to be a substantial positive predictor for lead time reduction meaning that a reduction in set up time leads to a significant reduction in lead time, hence improving the lead time performance.…”
Section: Lead Time Reductionmentioning
confidence: 99%
“…Time-based competition, lot sizing (production in small/large batches), continuous flow production and bottleneck removal are lean practices identified by de Treville et al (2004) to contribute positively in the reduction of lead times. Sharma et al (2015) performed multiple regression analysis to evaluate the impact of several lean manufacturing practices on lead time (The manufacturing practices being the independent variables). In their research, pull system was discovered to be a positive predictor (Nakamura et al, 1998;Sharma et al, 2015;Singh et al, 2013) while set up time reduction was observed to be a substantial positive predictor for lead time reduction meaning that a reduction in set up time leads to a significant reduction in lead time, hence improving the lead time performance.…”
Section: Lead Time Reductionmentioning
confidence: 99%
“…There are many researchers have discussed the relationship between lean practice and performance (e.g. operational performance and organizational performance, economic performance), these studies tested different lean practices influences on different performance dimensions, as there are an impact of lean practices on cost performance and non-cost performance (Chavez et al, 2013;Chavez et al, 2015;Taj & Morosan, 2011;Rahman et al, 2010;Harris & Cassidy, 2014;Koumanakos, 2008;Balakrishnan et al, 1996;Filho et al, 2016;Sharma et al, 2015;Shah & Ganji, 2017). In the transition to LSC performance, there are many authors discussed the impact of LSC practices on SC performance (Arif-Uz-Zaman & Ahsan, 2014; Tortorella et al, 2017;Nimeh et al, 2018;Abdallah et al, 2014).…”
Section: -3 Lean Practice and Supply Chain Performancementioning
confidence: 99%
“…performance measures were selected to evaluate SC performance based on the fact that these measures are the most common measures used in the majority of researches and recent in dates e.g. (Chavez et al, 2013;Taj & Morosan, 2011;Nawanir et al, 2016;Arif-Uz-Zaman & Ahsan, 2014;Ruiz-Benítez et al, 2018;Filho et al, 2016;Sharma et al, 2015;Shah & Ganji, 2017;Prajogo et al, 2016;Khanchanapong et al, 2014;Azfar et al, 2014;Dora et al, 2016;Kumar et al, 2015;Afonso & Cabrita, 2015;Droge et al, 2004, Jacobs et al, 2007Machuca et al, 2011;Rosenzweig et al, 2003;Folinas et al, 2014 ;Sangwa & Sangwan, 2018;Arif-Uz-Zaman & Ahsan, 2014;Behrouzi &Wong, 2011;Chavez et al, 2015). From which, the measures were classified into four different performance attributes (cost, time, quality, flexibility), those attributes are highly common in these researches that have discussed lean practice and performance topics.…”
mentioning
confidence: 99%
“…De fato, Taylor (2006) tangencia a incorporação dessa prática no contexto de implementação de LSCM. Contudo, somente em Sharma et al (2015) e Jasti e Kodali (2015) que esta foi explicitamente incluída no conjunto de práticas de LSCM. Assim, a partir da maior compreensão e expansão do pensamento enxuto para as cadeias de suprimentos, o qual proporcionou um enfoque muito mais abrangente quanto a implementação do LSCM, a P18 ganhou considerável atenção e começou a ser tratada como uma prática de LSCM.…”
Section: Práticas De Lscmunclassified
“…Tabela 2 -Práticas de LSCM e sua frequência de citação na literatura (Parte I) Autores (1) Hartono et al, 2015;(44) Jasti e Kodali, 2015b;(45) Olesen et al, 2015;(46) Sharma et al, 2015;(47) Vlachos, 2015;(48) Adebanjo et al, 2016;(49) Jajja et al, 2016;(50) Dora et al, 2016;(51) Soni e Kodali, 2016;(52) Marodin et al, 2016;(53) Carvalho et al, 2017b;(54) Duarte e Machado, 2017;(55) Bevilacqua et al, 2017.…”
Section: Práticas De Lscmunclassified